PROFESIONALISME GURU HONORER RELEVANSI ANTARA TUNTUTAN DAN KESEJAHTERAAN - Ratih Kesuma Dewi; Reninda Dewi Pinar (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2018)
The honorary teacher is integral part of an effort to educate the generation of the nation. The existence of honorary teacher cannot be separated from the national movement “Mental Revolution” triggered by the Indonesian government. It certainly puts the teachers’ role in a significant position as the educator. In line with that, the aim of national education is to educate life of the nation, but the obedience of the world of Indonesian education is due to social, economic and political problems, it makes distorted the educational goal further. Education in Indonesia leaves the same problems year after year. One of the crucial is welfare of teachers which is related to meager salaries, career training and quality of human resource. On the other hand, they are required to upgrade their quality continuously, intelligent, creative, innovative and work professionally